CO2 Utilization by Electrolytic Splitting to Carbon Nanotubes in Non‐Lithiated, Cost‐Effective, Molten Carbonate Electrolytes. (25th February 2022) - Wang, Xirui; Licht, Gad; Liu, Xinye; Licht, Stuart
Abstract: Carbon nanotubes (CNTs), have extraordinarily high tensile strength, electrical and thermal conductivity, and electrical storage capabilities. To date, CNTs have had limited use due to their high synthesis cost. The synthesis costs decrease when CNTs are prepared by transition metal nucleated molten electrolytic CO2 splitting, rather than by conventional chemical vapor deposition or arc deposition techniques. In addition to cost, a second advantage of CNT electrosynthesis is that the process consumes the greenhouse gas CO2 in its transformation to CNTs (and oxygen), providing a path to climate mitigation. However, electrolytic high yield, CNT syntheses has only been demonstrated with expensive lithiated electrolytes, such as pure or mixed Li2 CO3 . This study demonstrates, after several hundred failures, that carbon nanomaterials, can be synthesized from CO2 in non‐lithiated electrolytes. In the new sodium barium carbonate electrolytes, lower mobility due to the absence of lithium ions is overcome by: i) low current density; or ii) the introduction of oxides, such as BaO, to induce graphene walls to facilitate passage of larger cations during the process of growing CNTs; and/or iii) addition of specific transition metal nucleation agents, such as Fe2 O3 . The electrolysis uses inexpensive anodes and cathodes to form carbon nanomaterials, including straight and coiled CNTs. Abstract : A new high yield pathway to produce carbon nanotubes (CNTs) directly from atmospheric CO2 using the first Li‐free carbonate electrolyte molten electrolysis is demonstrated. Oxides and additional nucleation metals allow for higher conductivity and more energy favorable pathways for CNTs to form. The new Na and Ba carbonate electrolytes are an order of magnitude less expensive than comparable Li carbonate based electrolytes.